Complementary and Alternative Veterinary Medicine: Where Things Stand for Feline Health. Issue 4 (2nd October 2018) - Johnson, Kelly A.
ABSTRACT: As frustration with conventional medicine deepens, people are seeking novel approaches to health care for themselves and their pets. Not only are many alternative therapies comparatively inexpensive and readily available, they offer owners an opportunity to actively contribute to their pets' health. Hope surrounding alternative veterinary medicine is understandable, but for most modalities there is little evidence to support efficacy, and some pose significant risks to both humans and companion animals. Although there is little scientific research to report, this paper aims to inform on the safety and efficacy of select alternative modalities, with a focus on feline medicine.